Vulnerability Through Resilience? An Example of the Counterproductive Effects of Spatially Related Governance in Hamburg-Wilhelmsburg - Schmidt, Tobias (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
In dealing with perceived threats and hazards by coordinating and bundling diverse actors’ efforts, governance approaches potentially face a problem. Perceptions of threats as well as adequate action strategies aiming to build up resilience are both based on processes of social construction. Therefore, what at first sight seem to be promising strategies for building resilience for all actors can conversely be considered as new threats and vulnerabilities by particular actors due to their differing perceptions. Within the context of a governance that intends to increase resilience this can potentially cause counterproductive effects. This paper demonstrates this possibility by means of a social constructivist notion of vulnerability and resilience. Socio-spatial identity building processes between the “International Building Exhibition” (“Internationale Bauausstellung”: IBA) and actors in the local area of Hamburg-Wilhelmsburg are used as an empirical example. This paper illustrates that historically developed social knowledge in the form of socio-spatial identities and local discourses can play an important role because it influences the specific perceptions of local actors.